STRATEGIC COST ANALYSIS USING VALUE ANALYSIS TECHNIQUE AND ITS ROLE IN IMPROVING PRODUCT QUALITY AND ACHIEVING COMPETITIVE ADVANTAGE: APPLIED STUDY - Alaa Miran Hussein (Scholar Express Journals, 2024)
The research aims to study one of the contemporary cost and administrative techniques, which is the value analysis technique, in order to demonstrate its role in achieving competitive advantage in its four dimensions, which are represented by reducing costs, improving quality, and reducing the time for design, manufacturing, assembly, and marketing, in addition to providing sufficient flexibility in responding to changes that may occur in the renewed needs and desires of customers .The research community is represented by Iraqi industrial companies, while the research sample is represented by the public company. For rubber and tire industries This is based on data for the year 2022, and the focus was on two products, which are: The frame size is 24/1200 and the frame size is 20/1200 . After analyzing the research results using strategic cost management techniques, the most important results reached were that the value analysis technique can help economic units achieve competitive advantage through its ability to reduce costs and improve quality
Keywords: Strategic Planning; Tax Awareness